Isolamento, identificação e caracterização de linhagem de levedura quanto ao crescimento e fermentação utilizando meios sintéticos com pentoses e hidrolisado de bagaço de cana-de-açúcar - Martini, Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The search for new yeast species able to ferment pentoses is one of the challenges towards the difficulties involving the technology on the production of second generation ethanol. Besides, the usage of lignocelulosic residues demands a step of hydrolysis for the depolymerization of the hemicelulosic fraction. Acids have been used frequently due to the low cost and high efficiency. However, inhibitors may also be released along with the sugars, inhibiting the fermentative activity of the yeasts. In this context, this study aimed to isolate yeast strains from natural sources (sugar cane juice, bagasse and rhizosphere, and corn straw), the presumptive evaluation of the pentose fermentation ability and the identification of the selected strain, which was evaluated regarding the ability to grow and ferment pentose by using synthetic media under different environmental conditions as well as acid hydrolysates obtained from sugar cane bagasse. Among 350 isolates, 39 displayed fermentative activity of arabinose (56.4%) or xylose (38.5%) or both (5.1%). One of the yeast strains that showed both arabinose and xylose fermentation (number 311), isolated from sugar cane juice, was identified by the amplification of D1/D2 region of the 26S gene and ITS region from the ribosomal DNA as Meyerozyma guilliermondii. This strain was evaluated regarding the influence of the carbon source (glucose, xylose or arabinose), pH (3.5; 4.5; 5.5) and temperature (30 oC, 35 oC, 40 oC) upon the growth, and the influence of pH (4.5; 5.5) and temperature (30 oC, 35 oC) upon the fermentation of xylose in concentrations ranging from 40 g/L to 100 g/L in synthetic media. Varying initial pH values and temperatures of incubation did not result in differences in the specific growth rate of M. guilliermondii when growing in 20 g/L arabinose, xylose or glucose. In fermentation assays, the increase in the xylose concentration did not bring about a higher alcohol production. A...

A procura por novas espécies de leveduras capazes de fermentar pentoses é um dos desafios frente às dificuldades na tecnologia da produção de etanol de segunda geração. Além disso, a utilização de resíduos lignocelulósicos para tal fim requer uma etapa de hidrólise para a despolimerização da fração hemicelulósica. O emprego de ácidos tem sido utilizado frequentemente devido ao baixo custo e alta eficiência. Inibidores, no entanto podem também ser liberados juntamente com os açúcares, ocasionando inibição da atividade fermentativa das leveduras. Neste contexto, este estudo teve por objetivo realizar o isolamento de linhagens de leveduras de fontes naturais (caldo, bagaço e rizosfera de cana-de-açúcar, e palha de milho), a avaliação presuntiva da capacidade de fermentação de pentoses (Dxilose e L-arabinose) e a identificação da linhagem selecionada, a qual foi avaliada quanto à habilidade de crescimento e fermentação de pentoses utilizando meio sintéticos em diferentes condições ambientais assim como hidrolisados ácidos de bagaço de cana-de-açúcar. Dentre 350 isolados, 39 apresentaram atividade fermentativa de arabinose (56,4%) ou xilose (38,5%) ou ambas (5,1%). Uma das linhagens que apresentou fermentação tanto de arabinose quanto de xilose (código 311), isolada de caldo de cana-de-açúcar, foi identificada por meio da amplificação da região D1/D2 do gene 26S e da região ITS do DNA ribossomal como sendo da espécie Meyerozyma guilliermondii. Esta linhagem foi avaliada quanto à influência da fonte de carbono (glicose, xilose ou arabinose), pH (3,5; 4,5; 5,5) e temperatura (30 oC, 35 oC, 40 oC) sobre o crescimento, e à influência do pH (4,5; 5,5) e temperatura (30 oC, 35 oC) sobre a fermentação de xilose em concentrações variando de 40 g/L a 100 g/L em meios sintéticos. A variação nos valores de pH e temperatura não resultou em diferenças na velocidade específica de crescimento de...
Keywords: Fermentation; Fermentação; Levedos; Bagaço de cana; Microbiologia industrial